Electron microscopy of small nuclear ribonucleoprotein (snRNP) particles U2 and U5: evidence for a common structure-determining principle in the major U snRNP family. - Kastner, B (1990)
We have studied by electron microscopy the structures of native small nuclear ribonucleoprotein (snRNP) particles U2 and U5 from HeLa cells. The structure of native U2 snRNP is characterized by a main body 8 nm in diameter with one additional domain about 4 nm long and 6 nm wide. Electron micrographs show that the 20S U5 snRNP, which contains at least seven U5-specific proteins in addition to the common proteins, has an elongated structure measuring 20-23 nm in length and 11-14 nm in width. Two main structural domains can be distinguished: a small head and a large elongated body about twice the size of the head. In addition to the head, the body of the 20S U5 snRNP possesses three short protuberances. The U2 and U5 core RNP particles--that is, of the snRNPs U2 and U5 without the snRNP-specific proteins, look much simpler and smaller under the electron microscope. They both are round in shape with a diameter of approximately 8 nm. With respect to their size, appearance, and fine structure, the U2 and U5 snRNP cores not only closely resemble each other but also share these properties with the core domain of U1 snRNP. We propose that the characteristic shape of each of the major snRNP species U1, U2, U4/U6, and U5 is determined by (i) a core domain containing the proteins that are common to all members of this family, which has the same shape for each member, and (ii) peripheral structures, which for snRNPs U1, U2, and U5 arise from the specific proteins, that give each of these snRNP species its characteristic shape.